A functional representation of potential surprise ordering - Se Ho Kwak (University of Massachusetts, Department of Economics, 2022)
In the history of economic thought, Shackle was one of the representative critics about probability based economic theory. Specifically, he constructed his own concept of subjective uncertainty called potential surprise to replace probability. In 1980s, the potential surprise is axiomatized by Katzner as Kolmogorov-styled measure defined on the 𝜎-field over the set of possible states. In this paper, potential surprise function is reconstructed as the functional representation of potential surprise ordering on the space of hypotheses about future called monad.
Keywords: B21; B50; D81; 330; Shackle; uncertainty; probability